The Political Economy of Import-Substituting Industrialization in Latin America - Hirschman, Albert O. (Quarterly Journal of Economics, 1968)
Introduction: Disenchantment with industrialization in Latin America, 1. — I. Four impulses of import-substituting industrialization (ISI), 4. — II. Characteristics of the initial phase of ISI: industrialization by tightly separated stages, 6; "late" vs. "late late" industrialization, 8; the sources of entrepreneurship, 9; the exuberant phase of ISI and its political consequences, 11. — III. The alleged exhaustion of ISI, 13; a naive and a semi-naive exhaustion model, 13; criticism of the semi-naive model: the importance of policy, 14. — IV. Economic, political and technological determinants of backward linkage, 17. — V. The inability to export manufactures: "structural" causes and remedies, 24. — Conclusion, 31.